2014
DOI: 10.1039/c4cp01455c
|View full text |Cite
|
Sign up to set email alerts
|

Fe–N bonding in a carbon nanotube–graphene complex for oxygen reduction: an XAS study

Abstract: The electronic structure study of carbon nanotube-graphene complexes has been performed using comprehensive X-ray absorption spectroscopy (XAS) at Fe L- and K-edges, along with C, N and O K-edges. The results obtained from the study of an iron-containing carbon nanotube-graphene complex (NT-G) have been compared in great detail with those of an iron-free carbon nanotube-graphene complex (pNT-G) and iron phthalocyanine (FePc). It has been confirmed that complex-like Fe(3+) in a high spin state is the major iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 20 publications
6
61
0
Order By: Relevance
“…The decrease of the π* peaks could be attributed to coordination of nitrogen to H 3 PO 4 . The broadening and enhancement of the σ* (C‐N) peak suggest stronger C−N bonding, which may result from covalent NCHS and H 2 PO 4 − coupling . These observations demonstrated that H 3 PO 4 can block the active site of pyridinic N by connecting with N and adjacent C (inset in Figure b).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The decrease of the π* peaks could be attributed to coordination of nitrogen to H 3 PO 4 . The broadening and enhancement of the σ* (C‐N) peak suggest stronger C−N bonding, which may result from covalent NCHS and H 2 PO 4 − coupling . These observations demonstrated that H 3 PO 4 can block the active site of pyridinic N by connecting with N and adjacent C (inset in Figure b).…”
Section: Resultsmentioning
confidence: 92%
“…The π* peaks in the range of 398–402 eV can be divided into several characteristic peaks at 397.8 (pyridinic N), 400.5 (pyrrolic N), 401.4 (graphitic N), and 402.5 eV (pyridinic N‐O) . In addition to these peaks, some new features at 399.1 eV emerged, indicating that some of the pyridinic N atoms are bonded to Mo atoms . Furthermore, a broad peak at about 406 eV is found, which can be assigned to the σ* excitation of C−N bonds .…”
Section: Resultsmentioning
confidence: 97%
“…The Fe L ‐edge spectrum of the NP‐SP is shown in Figure c, which confirms the observation of XPS data that Fe species exist in the NP‐SP. Fe L ‐edge spectrum ( L 3 edge in the region of 706 to 712 eV and L 2 edge in the region of 718 to 726 eV) was aroused by electronic transitions between Fe 2p electrons and unoccupied 3d orbitals, and was further split by the ligand field due to the final state effect . In the L 3 edge region, a major peak at around 709.5 eV (peak a 1 ) and a shoulder peak at around 708.0 eV (peak a 2 ) can be observed, which suggests more contribution of high spin Fe 3+ in the NP‐SP due to possible incorporation of oxygen, as reported in the literature .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1 f, the Fe L-edge XANES spectrum of S,N-Fe/N/C-CNT exhibits a single peak at the L 3 -edge, which is distinctive for 3d-electrons, and no well-defined multiple structures are observed; the spectra bears a greater similarity to Fe rather than Fe-based oxides. [18] As shown in Figure 1 g, both spectra exhibit two features associated with sp 2 -hybridized carbon (a sharp p* peak and a doublet s* resonance peak), and the reduced peak intensities of S,N-Fe/ N/C-CNT indicate that the C 2p orbitals of the sample can be shared with the Fe 3d electrons. The itinerant Fe 3d-electrons can be shared by the porphyrin-like moieties and largely improve the electrical conductivity of the whole material system, which can be further confirmed by a comparison of the C K-edge XANES spectrum of S,N-Fe/N/C-CNT and S,N-/C-CNT.…”
mentioning
confidence: 88%
“…The itinerant Fe 3d-electrons can be shared by the porphyrin-like moieties and largely improve the electrical conductivity of the whole material system, which can be further confirmed by a comparison of the C K-edge XANES spectrum of S,N-Fe/N/C-CNT and S,N-/C-CNT. [18] As shown in Figure 1 g, both spectra exhibit two features associated with sp 2 -hybridized carbon (a sharp p* peak and a doublet s* resonance peak), and the reduced peak intensities of S,N-Fe/ N/C-CNT indicate that the C 2p orbitals of the sample can be shared with the Fe 3d electrons.…”
mentioning
confidence: 88%